Assessment of ventilation during swimming using backward extrapolation of the ventilation recovery curve - Kapus, J.; Usaj, A.; Kapus, V.; Strumbelj, B. (Kinesiology, 2004)
The purpose of the present study was to ascertain whether the backward extrapolation method can be used to calculate the pulmonary ventilation (VE) appropriate in two different breathing conditions during swimming: with and without reduced breathing frequency. Five trained swimmers swam 400 m front crawl at Onset of Blood Lactate Accumulation (OBLA) velocity taking a breath every stroke cycle (normal breathing - NB). Then they repeated 400-m front crawl at NB velocity and with NB stroke frequency taking a breath every second stroke cycle (restricted breathing - RB). The measures included the parameters of blood acid-base status (pH, Po2, Pco2, [HCO3-]) and pulmonary ventilation (VE). Pulmonary ventilation during swimming was obtained by the backward extrapolation method (VEe) and by a theoretical model (VEt). There was no significant difference between VEeand VEtin NB. But the paired t-test showed a significant (p<0,05) difference between these two parameters in RB. Pco2 was also significantly higher after RB than after NB. It may be concluded that the backward extrapolation method could be used to determine the VE during swimming without reduced breathing frequency. If exertion is caused by hypercapnia and/or acidosis (reduced breathing frequency during swimming) then the backward extrapolation method is questionable.